Quantification of in-season training load in Division I male collegiate soccer players - DeJohn, D. S.; Ryan, G. A.; Rossi, S. J. (The Journal of Sport and Exercise Science, 2022)
The purpose of this study was to quantify any differences in training load (TL), as measured via Duration, Heart rate (HR) and Session-Rating of Perceived Exertion Load (S-RPE Load), in Division I male collegiate soccer players. Training sessions during the fall competitive season were categorized by the days away from the next competition [match day (MD) out] in 26 collegiate soccer players. All training sessions were monitored using HR transmitter technology. HR data was expressed as percent of total practice duration spent in zones (%HRLow [. 69%], %HRMod [70-89%] and %HRHigh [. 90%]). A significant, main effect finding was noted for Duration (p < 0.01), S-RPE Load (p < 0.01), %HRLow (p < 0.01), %HRMod (p < 0.01), and %HRHigh (p < 0.01) between MD out from competition. Post hoc analysis revealed MD-1 had the lowest TL across all MDs. Load on MD-3 was greatest for Duration (90.72 } 23.78 min), S-RPE Load (1223.50 } 393.60 au), and %HRHigh (7.07 } 9.87). The highest load for %HRMod was on MD-4 (35.52 } 17.16 min), while %HRLow was on MD-1 (74.45 } 18.93 min). As MD approached, various trends, such as a bell-shaped curve (Duration, S-RPE Load, %HRHigh) and a linear taper (%HRMod), were evident. Periodization trends in internal and external TL are evident within the microcycle lens where the focus of training is on recovery and preparation for the forthcoming match.